CagA promotes proliferation and secretion of extracellular matrix by inhibiting signaling pathway of apoptosis in rat glomerular mesangial cells. (15th March 2016) - Wang, Li; Tan, Rui-Zhi; Chen, Yue; Wang, Hong-Lian; Liu, Yu-Hang; Wen, Dan; Fan, Jun-Ming
Abstract: Cytotoxin-associated antigen A (CagA), a major virulence factor of Helicobacter pylori (Hp), is associated with the pathogenesis of peptic ulcer and gastric cancer. Recent researches demonstrated that Hp exists in palatine tonsil in all studied IgA nephropathy (IgAN) patients, most of which were CagA-positive, suggesting that CagA may be a causative pathogenic factor of IgAN. However, the underlying molecular mechanisms and signaling pathway are still largely unclear. In the present study, CCK8 assay, enzyme-linked immunosorbent assay, and immunohistochemistry were performed to investigate the effect of CagA on cell proliferation and extracellular matrix secretion in rat glomerular mesangial cells. RT-PCR and western blotting were used to reveal the potential signaling pathway. Rat glomerular mesangial cells were treated with recombinant CagA protein for 72 h, in a dose- and time-dependent manner. We found that CagA promoted cell proliferation and extracellular matrix secretion by inhibiting signaling pathway of apoptosis. Taken together, these findings suggested that CagA induced cellular injury in glomerular mesangium by proliferation and secretion of extracellular matrix, and may play an important role in pathogenesis of IgAN.